Kritik Degrowth Ruang Terbuka Hijau sebagai Barang Publik di Surakarta: Literature Review - Prameswara, Yosep Tegar; Pratama, Ramadzan Defitri; Sari, Maya Rohmantika; Indriayu, Mintasih (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2025)
ABSTRACT Urbanization in Indonesia has led to the shrinking of Green Open Space (RTH), which is crucial for ecological balance and quality of life. Surakarta City has only 14% green space, far below the 30% standard set by Law No. 26/2007 on Spatial Planning. Degrowth offers an alternative approach that emphasizes ecological sustainability and social justice over exploitative economic growth. Within the framework of degrowth critique, this research examines green spaces as public goods, highlighting inequality of access and privatization of green spaces. This article uses a literature review method to analyze policies and challenges related to Green Open Space. The article examines the phenomenon from the perspective of economics, particularly in the context of public goods and externality theory. The results of this study indicate the need for more sustainability-oriented policies, with community-based management, strict regulation of green land privatization, and the use of green technology. This study offers an alternative perspective in spatial planning that is balanced between economic, social, and environmental aspects.